PREDICTIVE VALUE OF METABOLIC PROFILE IN ISCHEMIC HEART DISEASE WITH COMORBID ANXIETYDEPRESSIVE STATES - Nurillaeva, N.M.; Abdumalikov, F.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The global trend in the world of medicine is the search for effective methods of early detection on both clinical and biological level, through specific markers of anxiety-depressive disorders in patients with psychosomatic disorders. Given the wide prevalence and prognostic significance of depression in the manifestation of the clinical course and development of the early cardiovascular complications of interest is the study of the neurotoxic metabolites involved in the pathophysiology of depressive disorders as a possible biomarker for early diagnosis, prognosis, monitoring of patients with cardiac pathology.